Penundaan Makanan Padat Mengurangi Risiko Timbulnya Atopi pada Anak - Barlianto, Wisnu; Kusuma, HMS Chandra; HM, Ni Luh Putu (Jurnal Kedokteran Brawijaya, 2009)
Nutritions  plays  an  important  role  in  the  incidence  of  atopic  both  in  children  and  adults.  Several  recent guidelines  recommend  a  delay  of  solid  foods  to  prevent  atopic  disease.  However,  until  now,  there  is  still  much controversy  about  the  influence  a  delay  of  solid  foods  in  children  to  develop  atopic   disease.  This  study  aimed to  determine  the  impact  of  the  start  time  of  solid  foods  to  atopic  children.  A  case-control  study  was conducted in  outpatient  institutions  Pediatrics RSSA  Malang from  May 2008  until  May 2009.  Respondents were divided into two groups: atopic (cases) and non atopic (control) based on history of atopic disease. The age of first given  solid  food  and  familial  atopic  were retrieved  based  on  history .  Statistical analysis  using  Chi-square test at 95%    level  of confidence,  was conducted  to  determine the  impact  of the  start  time  of solid  food  to  the incidence  of  atopic.  There were 236  patients  divided  equally  into  atopic  and  control  group.  Giving solid  foods at 4-6 months of age will increase  the  risk  of atopic compared  with age> 6 months (OR  2.8 (1.29  to  6.07), p = 0.007).  The  results  of  this  study  support  the  recommendations  given  by  WHO, that  the  postponement  of  solid food  until  age  6  months  would  reduce  the  incidence  of  atopic  risk  in  children.Keywords  :  postponement  ,  solid  food,  atopic  diseases,  sensitization